Validation of a novel path planner for stereotactic neurosurgical interventions—A retrospective clinical study. Issue 6 (25th September 2022) - Wankhede, Ajeet; Madiraju, Likhita; Siampli, Eleni; Fischer, Elizabeth; Cleary, Kevin; Oluigbo, Chima; Monfaredi, Reza
Abstract: Background: The gold standard workflow for targeting structures in the brain involves manual path planning. This preoperative manual path planning is very time‐intensive and laborious, especially when some outcome measures such as maximum ablation and penetration depth has to be optimised. Methods: Our novel path planner generates an optimal path which maximises the hippocampus penetration and distance from critical structures using a precomputed cost map and a reward map. Results: The average penetration ratio for 12 cases is 88.13 ± 23.23% for a resolution of 1° and a safety margin of 1 mm. Average run time for the path planner based on 1° resolution was 1.99 ± 0.68 min. Conclusions: Results show that the algorithm can generate safe and clinically relevant paths with a quantitative representation of the penetration depth and is faster than the average reported time for manual path planning.